THE ARACEAE OF ITB JATINANGOR CAMPUS, SUMEDANG, WEST JAVA - Arifin Surya Dwipa Irsyam; Reza Raihandhany; Muhammad Rifqi Hariri; Rina Ratnasih Irwanto (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2021)
Araceae is a group of plants that are consistently dominant in humid and wet conditions areas. This family is among the most common plant groups found in the campus Institut Teknologi Bandung (ITB) at Jatinangor, which are still covered by green areas. However, the diversity of Araceae has not been revealed yet. Therefore, this research was conducted to provide information on the Araceae in ITB Jatinangor Campus. Field exploration was carried out during September - November 2021 at ITB Jatinangor. As many as 15 genera and 22 species of Araceae have been discovered within the campus. Taxonomically, they are grouped into 3 subfamilies, i.e Aroideae (12 genera), Monsteroideae (2 genera), and Pothoideae (1 genus). The largest genera of Araceae found on the campus were Anthurium and Philodendron, both cultivated as ornamental plants. Several local species, such as Alocasia macrorrhizos, Colocasia esculenta, Pistia stratiotes, Typhonium flagelliforme, and T. roxburghii were also found. Three other ornamental species have been escaped from cultivation, namely Caladium bicolor, Dieffenbachia seguine, and Syngonium podophyllum had were also found here. This research was part of the Flora Campus ITB Jatinangor Exploration, a project initiated by Herbarium Bandungense.